(untitled) (Anuário Antropológico, 2023)
Studying anthropology in Stockholm in the 1990s meant taking stock of the transnational turn within the discipline. I don’t know whether this was ever coined as an actual turn in its own right or whether it became subsumed in the ‘writing culture’ debate, but, in any case, being a young student in an increasingly interconnected world, it seemed only obvious to look at social relations and the making of cultural meaning through the concepts of flux and flow, mobility and boundaries, complexity and hybridity. We read the works by our own teachers – of which Hannerz (1992, 1996) was probably the most prominent – and by other anthropologists around the world analysing the production and effects of global relations. Among these latter works was a book called Transnational Capitalism and Hydropolitics in Argentina. The Yacyretá High Dam by Gustavo Lins Ribeiro (1994), which I read with great interest as a student of Latin American worlds. This was the first time I got to know his work. Little did I know then that his research would come to play a central role in my own studies many years later.